Assessment of perioperative minute ventilation in obese versus non-obese patients with a non-invasive respiratory volume monitor - Jaideep H. Mehta (BMC Anesthesiology, 2017)
Abstract Background Monitoring the adequacy of spontaneous breathing is a major patient safety concern in the post-operative setting. Monitoring is particularly important for obese patients, who are at a higher risk for post-surgical respiratory complications and often have increased metabolic demand due to excess weight. Here we used a novel, noninvasive Respiratory Volume Monitor (RVM) to monitor ventilation in both obese and non-obese orthopedic patients throughout their perioperative course, in order to develop better monitoring strategies. Methods We collected respiratory data from 62 orthopedic patients undergoing elective joint replacement surgery under general anesthesia using a bio-impedance based RVM with an electrode PadSet placed on the thorax. Patients were stratified into obese (BMI ≥ 30) and non-obese cohorts and minute ventilation (MV) at various perioperative time points was compared against each patient’s predicted minute ventilation (MVPRED) based on ideal body weight (IBW) and body surface area (BSA). The distributions of MV measurements were also compared across obese and non-obese cohorts. Results Obese patients had higher MV than the non-obese patients before, during, and after surgery. Measured MV of obese patients was significantly higher than their MVPRED from IBW formulas, with BSA-based MVPRED being a closer estimate. Obese patients also had greater variability in MV post-operatively when treated with standard opioid dosing. Conclusions Our study demonstrated that obese patients have greater variability in ventilation post-operatively when treated with standard opioid doses, and despite overall higher ventilation, many of them are still at risk for hypoventilation. BSA-based MVPRED formulas may be more appropriate than IBW-based ones when estimating the respiratory demand of obese patients. The RVM allows for the continuous and non-invasive assessment of respiratory function in both obese and non-obese patients.